Peace and its Discontents. Freud and Scheler on War and Death - Lohmüller, Torben (Revista de Filología Alemana, 2013)
Roughly 100 years after the outbreak of World War I this article reviews central positions taken by Freud and other early psychoanalysts with respect to the big subjects of war and peace. While Freud has often been perceived as a pacifist, an immediate comparison with the conservative philosopher Max Scheler and his eulogy to the Genius of War shows to what extend Freud is rooted in the spirit of his time. If even under different political premises, also Freud takes death and the violence of war to be the touchstone of civilization.